DEKOMPOSISI GRAF HELM - Rahayu, Risti Dwi; Kuswardi, Yemi (Journal of Mathematics and Mathematics Education, 2018)
Abstract: Decomposition of graph G is a collection of Hi from sub graph G until Hi = 〈Ei〉 for Ei subset E (G) and Ei is partitions of E (G). If Hi is a decomposition of G, it can be written as the addition of the sides and G is decomposed into sub graphs where n = |Hi|. In other words, is the decomposition of graph G. Helm Hn graph with n ≥ 3 and n is even number which can be partitioned into sub graph which is in the form of 2K2, where Hn = So, helmet Hn graph with n ≥ 3 and n is an even number of 2K2-decomposition. The Hn helm graph with n > 3 can be partitioned into sub graph Ai = 〈Ei〉 which is in the form of 3K2, where . So that the Hn helm graph with n > 3 is 3K2-decomposition.Keywords:Decomposition, Helm Graph.